EVALUATION OF CHANGE MANAGEMENT IMPLEMENTATION FOR THE ENHANCEMENT OF THE ELECTRONIC-BASED GOVERNMENT SYSTEM IN THE PROVINCIAL GOVERNMENT OF NORTH SUMATRA - Franky Sihaloho; Nazaruddin; Meilita Sembiring (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
This study aims to evaluate the implementation of change management to enhance the Electronic-Based Government System (SPBE) in the Provincial Government of North Sumatra by integrating the ITIL 4 approach into SPBE change management processes. A descriptive qualitative approach was employed to identify the strengths and weaknesses of the implementation through interviews, surveys, and document analysis. The findings reveal that the effectiveness of change management is influenced by policy readiness in the form of guidelines, the capacity of human resources to manage changes, and the stages of addressing changes supported by technological infrastructure. This study recommends developing a change management guideline that integrates ITIL 4 processes (risk identification, impact assessment, approval, implementation, and evaluation) with SPBE change management stages (planning, analysis, development, implementation, monitoring, and evaluation). Additionally, the establishment of a structured change management team and the development of systematic and iterative Standard Operating Procedures (SOPs) are suggested to ensure effective change management. The collaboration between the ITIL 4 approach and SPBE change management processes is expected to enhance the maturity level of change management, support sustainable digital transformation, and optimize the quality of electronic-based public services in the Provincial Government of North Sumatra.